Christopher Columbus - Krensky, Stephen; Green, Norman, 1934- (New York : Random House, 1991)
A simple account of Christopher Columbus' first voyage to America.
Keywords: Columbus, Christopher -- Juvenile literature; Columbus, Christopher; Explorers; America -- Discovery and exploration -- Spanish -- Juvenile literature; America -- Discovery and exploration -- Spanish